The Sacred Garden Versus the City of Man - Stanley Tigerman (Oz, 1989)
The desire to unravel the myths of origin is expressed in humankind's ceaseless effort to attain parity with the sacred garden by displacing it with the city of man. The determination to end our exile and be readmitted to Eden is played out in the envisioning of structures designed to give expression to nostalgic dreams of heaven..